Intrinsic anticipatory motives in non-human primate food consumption behavior - Judit Inkeller; Balázs Knakker; Péter Kovács; Balázs Lendvai; István Hernádi (iScience, 2024)
Summary: Future-oriented behavior is regarded as a cornerstone of human cognition. One key phenomenon through which future orientation can be studied is the delay of gratification, when consumption of an immediate reward is withstood to achieve a larger reward later. The delays used in animal delay of gratification paradigms are rather short to be considered relevant for studying human-like future orientation. Here, for the first time, we show that rhesus macaques exhibit human-relevant future orientation downregulating their operant food consumption in anticipation of a nutritionally equivalent but more palatable food with an unprecedentedly long delay of approximately 2.5 h. Importantly, this behavior is not a result of conditioning but intrinsic to the animals. Our results show that the cognitive time horizon of primates, when tested in ecologically valid foraging-like experiments, extends much further into the future than previously considered, opening up new avenues for translational biomedical research.